'I will empower him!': Representations of Prisoners' Wives in Russia. (October 2013) - Katz, Elena
<x content-type="archive" xml:space="preserve">Abstract</x> Representations of the experiences of past and present Russian prisoners' women relatives in Russia are explored. The annals of Russian national history glorify the handful of wives who voluntarily chose to share Siberian exile with their husbands who were punished for the anti-monarchist uprising in December 1825. A survey of images of prisoners' wives demonstrates how Russian cultural mythology has promoted a powerful, stereotypical image of the 'Decembrist wife' as the epitome of marital love, devotion and personal sacrifice. On the basis of various historic, literary, documentary and Internet sources, as well as interviews with current Russian prisoners' women relatives, the formation, articulation and enduring vitality of the 'Decembrist wife' discourse in Russia is examined.